2011
DOI: 10.2139/ssrn.1674068
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital and the Lifetime Costs of Impatience

Abstract: Note: The dependent variable reported in regression results uses the opposite of this variable, i.e. "No regular high school diploma by age 21".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 34 publications
7
88
3
1
Order By: Relevance
“…their patient counterparts (Cadena & Keys, 2015). Parents, who are an important influence on early-life education decisions, could potentially compensate for their children's poor self-control.…”
Section: Self-controlmentioning
confidence: 99%
“…their patient counterparts (Cadena & Keys, 2015). Parents, who are an important influence on early-life education decisions, could potentially compensate for their children's poor self-control.…”
Section: Self-controlmentioning
confidence: 99%
“…Typical choices include friendly/interested, cooperative, impatient/restless/bored, and hostile. Several studies have found that survey respondents rated as "impatient" by their interviewer behave in ways suggesting a difficulty with delaying gratification [1], [8]. The roughly 10-15% of individuals coded this way are more likely to smoke, less likely to have a bank account, more likely to drink to excess, and more likely to leave military service prior to the end of their initial commitments [1].…”
Section: Identifying Impatient Individualsmentioning
confidence: 99%
“…Another study uses the interviewer rating method discussed above to examine directly how impatience affects the high school dropout decision [1]. The key result is that impatient individuals are 56% more likely to drop out of high school than are patient individuals with similar characteristics.…”
Section: High School Completionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of empirical and experimental works confirms the relevance of inter-temporal and risk preferences for a very large number of domains such as education, (Belzil and Leonardi, 2007;Caner and Okten, 2010;Castillo et al 2011;Cadena and Keys, 2011;De Paola andGioia, 2012, 2013), labour market outcomes (Della Vigna and Paserman, 2005;Drago, 2006;Ahn, 2010;Dohmen and Falk, 2011;Pollmann et al 2012), health (Sutter et al, 2011;Golsteyn et al, 2012), immigration (Jaeger et al, 2010). Much less studied is the role of these variables on marriage, divorce and fertility.…”
Section: Introductionmentioning
confidence: 99%